2022
DOI: 10.1186/s13223-022-00653-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of peripheral neuropathy in a patient with antineutrophil cytoplasmic antibody-negative eosinophilic granulomatosis with polyangiitis by additional mepolizumab

Abstract: Background Eosinophilic granulomatosis with polyangiitis (EGPA) is a vasculitis characterized by abnormally high eosinophils and frequent peripheral neuropathy. Mepolizumab is an approved therapy for EGPA, but its efficacy against peripheral neuropathy remains unknown. Case presentation A 41-year-old woman was admitted in the hospital with dyspnea and neuropathy. Ground glass opacity and infiltrative shadow in the bilateral lungs were evident on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Whereas when diagnosed quickly and treated appropriately, prognosis is much improved, with a 78-month survival rate of about 70-90% [ 7 ]. Mepolizumab has been effectively used in combination with prednisolone to treat peripheral neuropathy associated with EGPA and most recently, add-on low-dose mepolizumab showed good results for long-lasting neuropathy complications from EGPA [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas when diagnosed quickly and treated appropriately, prognosis is much improved, with a 78-month survival rate of about 70-90% [ 7 ]. Mepolizumab has been effectively used in combination with prednisolone to treat peripheral neuropathy associated with EGPA and most recently, add-on low-dose mepolizumab showed good results for long-lasting neuropathy complications from EGPA [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Finalmente, la remisión dependerá del tratamiento inmunosupresor temprano, lo cual reduce notablemente la posibilidad de discapacidad a largo plazo. 9…”
Section: Discussionunclassified
“…De igual manera, esta enfermedad se presenta con mayor frecuencia en el sexo masculino, entre la quinta y sexta década de la vida, en pacientes con un promedio de edad de 50 años. [2][3][4][5][6][7][8][9] Cuando las vasculitis se asocian con anticuerpos anticitoplasma del neutrófilo (ANCA), se caracterizan por inflamación celular infiltrativa que causa necrosis de los vasos sanguíneos. Estos ANCA se detectan en dos tercios de los pacientes, comúnmente en los de mayor afectación sistémica y en general presentan un patrón perinuclear subtipo anti-mieloperoxidasa (p-ANCA-MPO) que puede contribuir en la patogenia e implicar así mecanismos autoinmunes.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Several attempts have been made to treat organ- or life-threatening manifestations of EGPA with mepolizumab, such as cardiomyopathy and gastrointestinal involvement [ 19 , 94 ], the efficacy of which is yet to be determined. However, a growing number of case reports and case series have shown that symptoms related to peripheral neuropathy were ameliorated and nerve conduction velocity tests improved with mepolizumab [ 95 , 96 , 97 ]. This appears promising, but the supporting evidence is currently insufficient.…”
Section: Updated Treatment Of Egpamentioning
confidence: 99%